Compression test and analysis of multi-limbs built-up cold-formed steel stub columns. (January 2017) - Liao, Fangfang; Wu, Hanheng; Wang, Ruizhi; Zhou, Tianhua
Abstract: Multi-limbs built-up cold-formed steel stub column is a main structural member consisting of a single C-shaped and U-shaped basic component connected by self-drilling screws. Axial compression bearing capacity tests and finite element analysis of nine multi-limbs built–up cold–formed steel stub columns with three different section forms were conducted in this paper. The results of finite element analysis are close to the test results, which verify the accuracy of the finite element analysis. In order to study the influence of width–thickness ratio and screw spacing on the bearing capacity of the build-up column, the parametric analysis was carried out on the maximum width–thickness ratio of the plates and the screw spacing. The results show that the failure modes of all specimens are local buckling and distortional buckling. Multi-limbs built–up cold–formed steel stub columns consisting of a few basic components can work in harmony, the integral behavior is desirable. The axial load bearing capacity of the multi-limbs built-up section stub column increases when the maximum width–thickness ratio of the plates decreases; the screw spacing has a little impact on the ultimate axial compressive capacity and the buckling capacity of the multi-limbs built-up cold-formed steel stub columns. Highlights: Axial compression tests of nine multi-limbs built–up cold–formed steel stub columns were conducted. The accuracy of finite element analysis was verified by test results. The axial bearing capacity of the column increases when the maximum width–thickness ratio of the plates decreases. The screw spacing has a little impact on the bearing capacity of the columns.